2000
DOI: 10.1007/s002130000395
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of behavioral sensitization by MK-801: fact or artifact?

Abstract: The studies reviewed herein have produced results both consistent with and in contradiction to the view that MK-801 and related drugs block behavioral plasticity, and the debate about how exactly MK-801 and related drugs interact with other drugs in sensitization experiments is still in full swing. What seems crucial for future studies relating to this subject is a careful experimental design to reduce the number of potential interpretations of the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…However, this conclusion is still highly controversial and the role of NMDARs in addiction remains unclear [78]. The problems with using MK801, including its non-specific side effects and paradoxical ability to induce sensitization to itself, have been reviewed extensively [34][35][36]. It has been repeatedly suggested that alternative antagonists, particularly competitive antagonists, be used in place of MK801.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this conclusion is still highly controversial and the role of NMDARs in addiction remains unclear [78]. The problems with using MK801, including its non-specific side effects and paradoxical ability to induce sensitization to itself, have been reviewed extensively [34][35][36]. It has been repeatedly suggested that alternative antagonists, particularly competitive antagonists, be used in place of MK801.…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies suggest a role for NMDARs in behavioral sensitization and conditioned place preference, such findings are difficult to interpret because of several serious side effects associated with MK801 administration [34][35][36]. MK801 acts within the NMDA calcium channel in a manner similar to phencyclidine (PCP) and ketamine, and can produce psychosis [37], catalepsy, analgesia, and locomotor hyperactivity.…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism by which MK-801 may exert its effect on conditioned responding is that N-methyl-D-aspartate receptor activation may be necessary for retrieval of the neural representation of a nicotine cue. Another possible explanation is that the co-administration of MK-801 with nicotine may create a drug state that is different from that in which the nicotine-sucrose association was learned (see Tzschentke and Schmidt, 2000; see also Wolf, 1998). For this latter possibility, MK-801 has served as an effective discriminative stimulus in operant drug discrimination work (Corbett, 1995, Smith et al, 1999and Zajaczkowski et al, 1996, and therefore, in our study, the addition of MK-801 to nicotine may be creating a distinct cue different from that of nicotine alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, this effect may occur, not because the NMDA antagonist disrupted the development of sensitization, but because sensitization that may have occurred to the NMDA antagonist/drug combination cannot be retrieved or expressed in the drug alone state (e.g. Tzschentke and Schmidt 2000). For example, Carlezon et al (1995) found that co-administration of 0.3 mg/kg dizocilpine along with the direct dopamine agonist bromocriptine during ten sensitization sessions reduced the subsequent expression of sensitization to a challenge injection of bromocriptine alone, as expected.…”
Section: Introductionmentioning
confidence: 96%